Strain‐Engineered Metal‐to‐Insulator Transition and Orbital Polarization in Nickelate Superlattices Integrated on Silicon. Issue 50 (11th November 2020) - Chen, Binbin; Gauquelin, Nicolas; Jannis, Daen; Cunha, Daniel M.; Halisdemir, Ufuk; Piamonteze, Cinthia; Lee, Jin Hong; Belhadi, Jamal; Eltes, Felix; Abel, Stefan; Jovanović, Zoran; Spreitzer, Matjaž; et al.
Abstract: Epitaxial growth of SrTiO3 (STO) on silicon greatly accelerates the monolithic integration of multifunctional oxides into the mainstream semiconductor electronics. However, oxide superlattices (SLs), the birthplace of many exciting discoveries, remain largely unexplored on silicon. In this work, LaNiO3 /LaFeO3 SLs are synthesized on STO‐buffered silicon (Si/STO) and STO single‐crystal substrates, and their electronic properties are compared using dc transport and X‐ray absorption spectroscopy. Both sets of SLs show a similar thickness‐driven metal‐to‐insulator transition, albeit with resistivity and transition temperature modified by the different amounts of strain. In particular, the large tensile strain promotes a pronounced Ni 3 d x 2 − y 2 orbital polarization for the SL grown on Si/STO, comparable to that reported for LaNiO3 SL epitaxially strained to DyScO3 substrate. Those results illustrate the ability to integrate oxide SLs on silicon with structure and property approaching their counterparts grown on STO single crystal, and also open up new prospects of strain engineering in functional oxides based on the Si platform. Abstract : Strain engineering is well demonstrated for perovskite oxides, mostly by growing epitaxial films onto an isostructural oxide substrate having a different lattice constant. The joint effects of epitaxial and thermal strain on the metal‐to‐insulator transition and orbital configuration are revealed for nickelate superlattices grown on silicon substrates, illustrating the feasibility of extending strain engineering to the technologically important silicon platform.